2007
DOI: 10.1093/pcp/pcl062
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Coptis japonica Norcoclaurine 6- O -Methyltransferase Overcomes the Rate-Limiting Step in Benzylisoquinoline Alkaloid Biosynthesis in Cultured Eschscholzia californica

Abstract: Benzylisoquinoline alkaloids are one of the most important secondary metabolite groups, and include the economically important analgesic morphine and the antimicrobial agent berberine. To improve the production of these alkaloids, we investigated the effect of the overexpression of putative rate-limiting step enzymes in benzylisoquinoline alkaloid biosynthesis. We introduced two O-methyltransferase [Coptis japonica norcoclaurine 6-O-methyltransferase (6OMT) and 3'-hydroxy-N-methylcoclaurine 4'-O-methyltransfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 26 publications
3
62
0
Order By: Relevance
“…82) This robust metabolism should help plant cells, to adapt to biochemical changes, and cultured plant cells are a suitable system for testing evolutional diversification, since they have strong potential for somaclonal variation. 78,86) These results also suggest that enzymes in secondary metabolism might have broad substrate-specificity and high adaptability to metabolic modification induced by spontaneous genetic modification. Cultured cells with a modified metabolic pathway might be useful in tracing the evolution of metabolism.…”
Section: Metabolic Engineering In Cultured Cellsmentioning
confidence: 77%
See 1 more Smart Citation
“…82) This robust metabolism should help plant cells, to adapt to biochemical changes, and cultured plant cells are a suitable system for testing evolutional diversification, since they have strong potential for somaclonal variation. 78,86) These results also suggest that enzymes in secondary metabolism might have broad substrate-specificity and high adaptability to metabolic modification induced by spontaneous genetic modification. Cultured cells with a modified metabolic pathway might be useful in tracing the evolution of metabolism.…”
Section: Metabolic Engineering In Cultured Cellsmentioning
confidence: 77%
“…4A), whereas overexpression of C. japonica 4 0 OMT had only a marginal effect. 78) Overexpression of 4 0 OMT in a homologous host, the C. japonica plant, however, resulted in a marked increase in the amount of alkaloids, whereas transgenic C. japonica plants that overexpressed Cj4 0 OMT showed slower growth than the wild type. 79) Many experiments have indicated that the overexpression of other biosynthetic enzymes in various host plants has various effects, and thus suggest that more intensive studies of metabolic flow in various types of target-plant cells, are essential for continued progress in metabolic engineering, and especially to improve yields, through overexpression of rate-limiting enzymes.…”
Section: Metabolic Engineering In Cultured Cellsmentioning
confidence: 99%
“…Inc., Osaka, Japan) at 20°C in the dark. After preculture, the segments were co-cultured with the A. tumefaciens strain LBA4404 harboring pBHE4′ (vector for overexpression of Cj4′OMT 12) ) for 2 d in WPGN1K2 liquid medium containing 2% sucrose; then bacteria was eliminated on WPGN1K2 medium containing 500 mg/L claforan (Sanofi Aventis, Tokyo, Japan). After 1 to 2 months, the segments which formed calli and adventitious roots were cultured on WPGN1K2 medium containing 25 mg/L hygromycin at 20°C in the dark.…”
Section: Transformation and Plant Regenerationmentioning
confidence: 99%
“…11) Overexpression of Cj6OMT in Ec-cultured cells also resulted in an effective increase of benzophenanthridine alkaloids. 12) On the other hand, suppression of the biosynthetic pathway showed more prominent and complicated results. RNAi suppression of PsCOR resulted in the surprising accumulation of reticuline, which is 7 enzymatic steps upstream of COR.…”
mentioning
confidence: 99%
“…While some OMTs in isoquinoline alkaloid biosynthesis have been reported to have strict substrate specificity and reaction specificity, 9) a recent re-investigation of some enzymes showed that 3 0 -hydroxy-N-methylcoclaurine 4 0 -O-methyltransferase (4 0 OMT) not only contributes to 4 0 -Omethylation but also to the 6-O-methylation of norcoclaurine. 17) Furthermore, characterization of a chimeric enzyme of norcoclaurine 6-O-methyltransferase and 4 0 -OMT showed that their substrate specificity and reaction specificity can be modified by substitution in the Nterminal region, which might be involved in substrate binding. 18) IpeOMT2 has glutamic acid, asparagine, and methionine at positions 5, 63, and 121 respectively, while CiOMT1 has glutamine, lysine, and leucine at these positions.…”
Section: Substrate Specificity and Affinity Of Ciomt1mentioning
confidence: 99%